Infrastructure and gowth : empirical evidence - Balázs Égert; Tomasz Kozluk; Douglas Sutherland (Center for Economic Studies and ifo Institute (CESifo), 2009)
Investment in network infrastructure can boost long-term economic growth in OECD countries. Moreover, infrastructure investment can have a positive effect on growth that goes beyond the effect of the capital stock because of economies of scale, the existence of network externalities competition enhancing effects. This paper analyses the empirical relationship between infrastructure and economic growth. Time-series results reveal a positive impact of infrastructure investment on growth. They also show that this effect varies across countries and sectors and over time. In some cases, these results reveal evidence of possible over-investment. Bayesian model averaging of cross-section growth regressions confirms that infrastructure investment in telecommunications and the electricity sectors has a robust positive effect on long-term growth (but not in railways and road networks). Furthermore, this effect is highly nonlinear as the impact is stronger if the physical stock is lower.
Keywords: E22; O11; O40; 330; investment; infrastructure; network industry; economic growth; cointegration; Bayesian model averaging; Infrastruktur; Infrastrukturinvestition; Wirtschaftswachstum; Netzinfrastruktur; Schätzung; OECD-Staaten